The effects of CEO greediness and peer compensation on the quality of firms’ financial information - Alhossini, Abdullah A. (2024)
Given the severe consequences of low-quality financial information from firms—such as eroding investor trust and even triggering financial crises—its determinants have drawn significant attention from regulators, investors, and researchers. Nevertheless, serious oversights prevail in the accounting literature, particularly concerning greedy CEOs, who harbor intense desires for extraordinary material wealth at others’ expense, jeopardize firms’ sustainability, and even contributed to recent financial scandals. Specifically, despite their various social and organizational implications, the effects of CEO greediness on the quality of firms’ financial information have been neglected. The current thesis, however, fills this gap in the existing literature by investigating both the separate then the integrated impacts of CEO greediness along with CEO compensation at peer firms on financial information quality. First, using a 1992–2019 U.S. sample with 23,837 firm-year observations and three proxies for measuring CEO greediness, the research findings demonstrate a positive association between CEO greediness and the extensive use of earnings management, ranging from accrual-based earnings management, real earnings management, and classification shifting to opportunistic non-GAAP earnings disclosure. These findings highlight the multifaceted approach to earnings management that greedy CEOs employ. Moreover, the research finds that external auditors charge higher fees to and are more likely to resign from clients with greedy CEOs, indicating auditors’ perceived risk of CEO greediness on financial information quality. When comparing changes in earnings management practices and auditors' decisions around CEO transitions— where incoming and outgoing CEOs exhibit varying levels of greediness—it reinforces the study's conclusion that CEO greediness adversely affects the quality of a firm's financial information. Next, investigating the influences of peer firms’ CEO compensation on a firm’s financial information quality, this study—using a text-based measure to identify peer firms and a consequent 1992–2019 sample of 23,371 observations—finds a negative association between peer firms’ CEO compensation and a firm’s financial information quality, as measured by accrual-based and real earnings management, classification shifting, and non-GAAP earnings. The findings also show a positive relationship between peers’ CEO compensation and both external audit fees and auditor resignations. Finally, examining the moderating role CEO greediness plays in the peer compensation-information quality nexus, this study finds that CEO greediness exacerbates the above negative association and renders the above positive relationships more pronounced. Overall, the findings suggest that as peers' CEO compensation rises, the focal CEO is more likely to employ varied earnings management strategies to boost their personal gains, with CEO greediness significantly intensifying this relationship. The research contributes to the literature on CEO greediness, compensation, and financial information quality. The findings emphasize the significant role of CEO greediness and peers’ CEO compensation in shaping the quality of firms' financial information, providing valuable insights for shareholders, regulators, and broader corporate governance. Theoretically, the research emphasizes the notion that CEO personality traits interact with economic incentives they face to affect CEO decisions, thereby further enhancing understanding of the variations in behavioral responses to incentives such as peer compensation. Methodologically, the study integrates four dominant measures of earnings management to capture a holistic picture of information quality while also considering auditors' perspectives, thereby expanding the extant literature’s narrow focus on limited measures, despite the potential substitute nature intrinsic to these measures.